2004
DOI: 10.1016/j.biopsych.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Depression and 24-hour urinary cortisol in medical outpatients with coronary heart disease: The Heart and Soul Study

Abstract: Background-In patients with coronary heart disease (CHD), depression leads to worse cardiovascular outcomes. Depression has been associated with increased cortisol in medically healthy patients, suggesting that cortisol may act as a mediator in the pathway between depression and cardiovascular events. However, it is not known whether depression is associated with elevated cortisol levels in patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 60 publications
5
70
1
2
Order By: Relevance
“…In turn, norepinephrine enhances forebrain CRF activity, possibly closing a feed-forward loop leading to higher activity of both norepinephrine and CRF in depressed patients (37). Indeed, in this study group, we also found increased cortisol levels in depressed patients (42), consistent with this model of norepinephrine-CRF interaction (10).…”
Section: Discussionsupporting
confidence: 83%
“…In turn, norepinephrine enhances forebrain CRF activity, possibly closing a feed-forward loop leading to higher activity of both norepinephrine and CRF in depressed patients (37). Indeed, in this study group, we also found increased cortisol levels in depressed patients (42), consistent with this model of norepinephrine-CRF interaction (10).…”
Section: Discussionsupporting
confidence: 83%
“…Our study provides evidence for the proposition that elevated cortisol levels increase the risk of the metabolic syndrome. An association between urinary cortisol and metabolic parameters was not observed in a study by Otte et al (2004); however this study did not investigate the metabolic syndrome as a whole and did not examine depression*cortisol interactions. Most importantly, our study confirmed the hypothesis that when both depression and high cortisol levels are present, the odds of the metabolic syndrome is increased.…”
Section: Discussionmentioning
confidence: 72%
“…Details regarding our recruitment procedures have been published previously (23)(24)(25). In brief, we used administrative databases to identify outpatients with documented coronary disease at two Department of Veterans Affairs (VA) medical centers in California (San Francisco VA Medical Center and VA Palo Alto Health Care System), one university medical center (University of California, San Francisco), and nine public health clinics in the Community Health Network of San Francisco.…”
Section: Methods Participantsmentioning
confidence: 99%